The Green Hotel Concept As A Model Of Sustainable Accommodation Facilities - Vanessa Jaklin; Wiwik Nirmala Sari (Mutiara: Multidiciplinary Scientifict Journal, 2023)
Green-hotel is a concept in the accommodation industry that integrates sustainable practices to reduce environmental impact and encourage social responsibility. This study aims to explain and evaluate the concept of green-hotel as a model of sustainable accommodation facilities. This concept includes the use of environmentally friendly technology, efficient resource management, and community involvement in sustainable efforts. The study notes that green hotels can reduce energy, water, and waste consumption and promote the use of recycled materials. In addition, green hotels also implement social practices such as training the local workforce, promoting local culture, and supporting the local economy. In the context of climate change and growing environmental awareness, the green hotel concept provides a clear view of how the accommodation industry can play a role in preserving the environment and improving the quality of life of local communities. Thus, green hotels are a model of sustainable means of accommodation that have the potential to bring significant economic, social, and environmental benefits.